External beam pulsed low dose radiotherapy using volumetric modulated arc therapy: Planning and delivery. Issue 1 (13th December 2012) - Tyagi, Neelam; Yang, Kai; Sandhu, Raminder; Yan, Di; Park, Sean S.; Chen, Peter Y.; Marples, Brian
Abstract : Purpose: : To evaluate the feasibility of planning and delivering pulsed low dose radiotherapy (PLRT) using volumetric modulated arc therapy (VMAT) on Elektalinacs. Methods: : Ten patients previously treated for glioblastomamultiforme (GBM) were replanned using PLRT VMAT to deliver ten 0.2 Gy pulses separated by 3 min intervals with an effective dose rate of 0.067 Gy/min. VMAT parameters such as leaf speed and arc length were investigated to deliver 2 Gy/fraction to a total of 60 Gy to the target volume in ten subfractions or pulses. Plan quality was assessed using conformity and homogeneity indices. Absolute dose distribution for individual pulses was measured using ArcCHECK diode array. Individual pulses were analyzed for reproducibility and stability using machine log files. Machine characteristics at low monitor units and low dose rate were also investigated. Results: : An optimal arc length of 140°–160° and a leaf speed of 0.18–0.25 cm/° were sufficient to provide equivalent plan coverage and stable delivery. The average time and dose rate required to deliver a single 0.2 Gy pulse was 39.5 ± 2.3 s and 49 ± 32.3 cGy/min. Average reductions in MUs for the VMAT PLRT plan compared to IMRT for PTV was 16% (Range: −5.5%–36.1%) and 10.9% (Range: −18.4%–32.3%) for the initial and boost plan. A significant improvement was seen in maximum doses to all sensitive structures when planned with VMAT PLRT. The average absolute dose gamma passing rate for the 10 pulses combined and 2 Gy plan were 91.6 ± 2.5% and 97.3 ± 1.2%, respectively. Cumulative monitor units, dose rate, gantry angles, and leaf positions evaluated using machine log files were within 2% for all pulses. Conclusions: : Elekta linacs are capable of delivering reproducible and stable PLRT plans. A prospective clinical study employing PLRT is currently in development.